Medication-related osteonecrosis of the jaw-A case report and literature review - Chen, Chieh; Liao, Da-Ming (Archives of Community Medicine and Public Health, 2023)
Osteoporosis is a skeletal disease caused by changes in the structure of the human skeleton, resulting in fragile and easily fractured bones. Because it is more common in postmenopausal women or the elderly, fractures may cause disability in the elderly, resulting in reduced quality of life, bedridden, or increased mortality. Therefore, the treatment of osteoporosis is one of the important issues in today’s aging society. In addition, diseases such as bone metastasis of cancer and multiple myeloma also need to be paid attention to. Drugs for the treatment of osteoporosis have been widely used in the prevention and treatment of osteoporosis because of their inhibitory effect on osteoclast activity, and even become the first-choice drug for bone metastases of some malignant tumors. Drugs for the treatment or prevention of osteoporosis can inhibit osteoclasts, and can also be used to treat hypercalcemia complications of malignant tumors or bone-related systemic diseases. For example, bisphosphonates or monoclonal antibody preparations (eg: Denosumab, Romosozumab, etc.) can resist bone resorption. However, in recent years, the literature pointed out that patients using anti-bone resorption drugs may have adverse reactions to maxillofacial osteonecrosis. Medication-Related Osteonecrosis of the Jaw (MRONJ) may occur in patients with osteoporosis and tumors. Bisphosphonates or synthetic human monoclonal antibodies can inhibit bone resorption and are currently the most commonly used drugs for the treatment of osteoporosis in the world. The literature for nearly 20 years has shown that long-term use of such antiresorptive drugs increases the risk of osteonecrosis of the jaw in the oral cavity. Therefore, MRONJ is still a complication that we must pay attention to. Once MRONJ occurs, it is recommended to refer to an oral surgeon immediately; the current clinical treatment methods include the use of antibacterial mouthwash and drugs to control pain in mild cases, and antibiotics for infection control in moderate cases.